How water availability influences morphological and biomechanical properties in the one-leaf plant Monophyllaea horsfieldii. Issue 1 (3rd January 2018) - Kampowski, Tim; Mylo, Max David; Poppinga, Simon; Speck, Thomas
Abstract : In its natural habitat, the one-leaf plant Monophyllaea horsfieldii (Gesneriaceae) shows striking postural changes and dramatic loss of stability in response to intermittently occurring droughts. As the morphological, anatomical and biomechanical bases of these alterations are as yet unclear, we examined the influence of varying water contents on M. horsfieldii by conducting dehydration–rehydration experiments together with various imaging techniques as well as quantitative bending and turgor pressure measurements. As long as only moderate water stress was applied, gradual reductions in hypocotyl diameters and structural bending moduli during dehydration were almost always rapidly recovered in acropetal direction upon rehydration. On an anatomical scale, M. horsfieldii hypocotyls revealed substantial water stress-induced alterations in parenchymatous tissues, whereas the cell form and structure of epidermal and vascular tissues hardly changed. In summary, the functional morphology and biomechanics of M. horsfieldii hypocotyls directly correlated with water status alterations and associated physiological parameters (i.e. turgor pressure). Moreover, M. horsfieldii showed only little passive structural–functional adaptations to dehydration in comparison with poikilohydrous Ramonda myconi .